Work design improvement of food steamer at Pau Mira Frozen Food Industry - Junaidi, Adiliya Hellanie; John, Fredilla Ivy Tijah; Osman, Muhammad Yusra; Saadan, Muhammad Zainul Ariffin; Mahmood, Salwa; Saleh, Aslinda (Penerbit UTHM, 2020)
Pau Mira is a frozen food company located at kilometer 13, Kampung Tanah Merah, Pagoh Muar, Johor. It was devloped by a family in Kampung Tanah Merah. Pau Mira was initially made and sold daily, nearby the road side. Currently, the brand has continued to flourish in the food industry when its entrepreneur Mr. Misnan Ramijo, succeeded in establishing a company to supply increasingly popular frozen food especially its main product which is the frozen ‘pau mira’. The pau is a traditional and local steamed bun made of flour and yeast with various filling inside. It is also called as bao or baozi which is well known in the chinese cuisine. However, the term pau will be further used in this chapter.